2017
DOI: 10.3389/fgene.2017.00183
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-catenin Signaling Pathway Regulates Specific lncRNAs That Impact Dermal Fibroblasts and Skin Fibrosis

Abstract: Wnt/β-catenin signaling is required for embryonic dermal fibroblast cell fate, and dysregulation of this pathway is sufficient to promote fibrosis in adult tissue. The downstream modulators of Wnt/β-catenin signaling required for controlling cell fate and dermal fibrosis remain poorly understood. The discovery of regulatory long non-coding RNAs (lncRNAs) and their pivotal roles as key modulators of gene expression downstream of signaling cascades in various contexts prompted us to investigate their roles in Wn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 69 publications
0
32
0
Order By: Relevance
“…GRN is found to be up-regulated in neurodegenerative diseases such as AD and multiple sclerosis and may also function in neuro-inflammation [ 65 , 66 , 67 ]. Another lncRNA whose expression was increased by lipotoxic injury in male hippocampal microvessels was Gm12603 (WINCR1), important in collective cell migration and collagen contraction [ 68 ], suggesting that lipotoxic injury-activated WINCR1 might affect endothelial cell migration and contractibility, and also potentially endothelial permeability.…”
Section: Discussionmentioning
confidence: 99%
“…GRN is found to be up-regulated in neurodegenerative diseases such as AD and multiple sclerosis and may also function in neuro-inflammation [ 65 , 66 , 67 ]. Another lncRNA whose expression was increased by lipotoxic injury in male hippocampal microvessels was Gm12603 (WINCR1), important in collective cell migration and collagen contraction [ 68 ], suggesting that lipotoxic injury-activated WINCR1 might affect endothelial cell migration and contractibility, and also potentially endothelial permeability.…”
Section: Discussionmentioning
confidence: 99%
“…The lower number of FOXC1 + cells can disrupt the ability of the meninges to deposit laminin and maintain the BM which leads to BM defects (Zarbalis et al, ). We previously found that β‐catenin signaling transcriptionally regulates mRNA expression of extracellular matrix (ECM) genes, such as Laminin , proteoglycans, and other ECM modulating proteins in embryonic and adult dermal fibroblasts (Budnick et al, ; Hamburg‐Shields, DiNuoscio, Mullin, Lafayatis, & Atit, ; Mullins et al, ). The trophic factors originating from the non‐meningeal mesenchyme in the basolateral site appears to be β‐catenin‐dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Yuan et al (2019) Wincr1 was found to be activated by Wnt/-catenin signaling pathway in fibroblast cells. (Mullin et al, 2017) So Wincr1 might be the downstream target of Wnt signaling pathway during adipogenesis. In short, during the early adipogenesis, Wnt/-catenin signaling pathway was inhibited by the down-regulations of Kcnq1ot1, Malat1, Hotairm1 and Mir17hg and the up-regulation of Gas5 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Wincr1, or Wnt signaling-Induced Non-Coding RNA 1, was downregulated by 0.29-fold, FDR 2.0x10-9 after 2 days of differentiation. Mullin et al (2017) reported that Wincr1 was induced by -catenin activity during skin fibrosis as its name suggests. Wincr1 further regulates the expression of key markers of dermal fibrosis.…”
Section: Identification Of Lncrnas That Significantly Changed Expressmentioning
confidence: 99%